No Taxation for Menstruation: The Book’s Role in Menstrual Activism - Barth, Ellen (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
This article addresses the role of books about menstruation in twenty‑first century menstrual activism. It argues that such books support and inspire transnational activist efforts by increasing public visibility of a taboo topic and by influencing perceptions about menstruation through their contents. Books on menstruation localize issues for specific linguistic, political, and cultural arenas, while still connecting to and bolstering the transnational movement. After providing an overview of current book trends, the article examines a single book, The Tampon Book, which protested the German tampon tax by hiding tampons in a book—a good with a lower tax rate than tampons. Materially embodying menstrual discrimination, the book contributed to activist efforts that led to the elimination of the tampon tax in Germany. Moreover, through engagement in the post‑digital publishing field, the book helped bring greater visibility to this internationally relevant issue.